Exceptional Framework Flexibility and Sorption Behavior of a Multifunctional Porous Cuprous Triazolate Framework - Zhang, Jie-Peng; Chen, Xiao-Ming (Journal of the American Chemical Society, 2008)
The porous metal azolate framework [Cu(etz)]∞ (MAF-2, Hetz = 3,5-diethyl-1,2,4-triazole) processes an NbO type cuprous triazolate scaffold and a CsCl type hydrophobic channel system, in which the large cavities are interconnected by small apertures with pendant ethyl groups. Since the ethyl-blocked apertures behave as thermoactivated IRIS stops for the guest molecules, the gas sorption behavior of MAF-2 can be controlled by temperature, in which N2 adsorption was observed at 195 K rather than 77 K. Single-crystal X-ray structural analysis revealed that the [Cu(etz)]∞ host framework is not altered upon N2 inclusion, confirming the occurrence of the so-called “kinetically controlled flexibility”. By virtue of the kinetically controlled flexibility and hydrophobic pore surface, MAF-2 can adsorb large amounts of small organic molecules but excludes H2O. As demonstrated by single-crystal X-ray structural analyses, MAF-2 shrinks, expands, or distorts its framework to accommodate the hydrogen-bonded hexamers of MeOH, EtOH, or MeCN, respectively. Moreover, MAF-2 can also separate benzene and cyclohexane efficiently, as its flexible scaffold can distort to a certain degree so that benzene can diffuse through the distorted apertures but cyclohexane cannot. Moreover, the adsorption/desorption of these organic vapors induces reversible, multimode structural transformations.